Flux density variability of 286 radio pulsars from a decade of monitoring. Issue 3 (21st December 2020) - Kumamoto, H; Dai, S; Johnston, S; Kerr, M; Shannon, R M; Weltevrede, P; Sobey, C; Manchester, R N; Hobbs, G; Takahashi, K
ABSTRACT: The Parkes telescope has been monitoring 286 radio pulsars approximately monthly since 2007 at an observing frequency of 1.4 GHz. The wide dispersion measure (DM) range of the pulsar sample and the uniformity of the observing procedure make the data set extremely valuable for studies of flux density variability and the interstellar medium (ISM). Here, we present flux density measurements and modulation indices of these pulsars over this period. We derive the structure function from the light curves and discuss the contributions to it from measurement noise, intrinsic variability, and interstellar scintillation. Despite a large scatter, we show that the modulation index is inversely correlated with DM, and can be generally described by a power law with an index of ∼−0.7 covering DMs from ∼10 to 1000 cm −3 pc. We present refractive time-scales and/or lower limits for a group of 42 pulsars. These often have values significantly different from theoretical expectations, indicating the complex nature of the ISM along individual lines of sight. In particular, local structures and non-Kolmogorov density fluctuations are likely playing important roles in the observed flux density variation of many of these pulsars.